Melting Curve and Phase Relations of Fe‐Ni Alloys: Implications for the Earth's Core Composition. Issue 14 (14th July 2020) - Torchio, R.; Boccato, S.; Miozzi, F.; Rosa, A. D.; Ishimatsu, N.; Kantor, I.; Sévelin‐Radiguet, N.; Briggs, R.; Meneghini, C.; Irifune, T.; Morard, G.
Abstract: Nickel is the second most abundant element in the Earth's core. However, the properties of Fe‐Ni alloys are still poorly constrained under planetary cores conditions, in particular concerning the effect of Ni on the melting curve of Fe. Here we show that Ni alloying up to 36 wt% does not affect the melting curve of Fe up to 100 GPa. However, Ni strongly modifies the hexagonal‐closed‐packed/face‐centered‐cubic (hcp/fcc) phase boundary, pushing the hcp/fcc/liquid triple point of Fe‐20wt%Ni to higher pressures and temperatures. Our results allow constraining the triple point for Fe‐10wt%Ni, a composition relevant for the Earth interior, and point out a decrease of the melting temperature at core‐mantle boundary by 400 K with respect to pure Fe. A lower amount of light elements than previously predicted is thus required to reduce the crystallization temperature of core materials below that of a peridotitic lower mantle, in better agreement with geochemical observations. Plain Language Summary: The Earth's core is believed to be composed of Fe alloyed with Ni and several lighter elements. In this paper, we investigate the effect of Ni alloying on the Fe phase diagram. The main effect of Ni addition is to enlarge the pressure/temperature stability domain of the face‐centered‐cubic (fcc) phase with respect to the hexagonal‐closed‐packed (hcp) phase and to shift the hcp/fcc/liquid triple point to higher pressures and temperatures. This implies a depression of the melting curve of Fe‐Ni alloys by around 400 K at mantle boundary conditions, at Ni concentrations pertinent for the Earth interior. This consequently decreases the temperature of the liquidus for Fe alloys constituting the Earth's core, in turn implying a reduced amount of light elements than previously predicted. Key Points: Melting curve and phase diagram of Fe‐20wt%Ni and Fe‐36wt%Ni have been investigated by in situ X‐ray absorption up to 120 GPa and 3500 K Ni alloying shifts the hcp/fcc/liquid triple point to higher pressures and temperatures The triple point for Fe‐10wt%Ni is predicted to be around 135 GPa and 3800 K fixing new benchmarks for the Earth's core composition